2023
DOI: 10.3390/antibiotics12010152
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Gene Interactions Reduce Aminoglycoside Susceptibility of Pseudomonas aeruginosa through Efflux Pump-Dependent and -Independent Mechanisms

Abstract: Pseudomonas aeruginosa causes a wide range of acute and chronic infections. Aminoglycosides are a cornerstone of treatment, but isolates are often resistant. The purpose of this research was to better understand the genetic basis of aminoglycoside resistance in P. aeruginosa. Bioinformatic approaches identified mutations in resistance-associated genes in the clinical isolates of P. aeruginosa. The common mutations were then engineered into the genome of P. aeruginosa reference strain PAO1. Mutations in the elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Naturally occurring mutations in the fusA1 gene have been linked to enhanced resistance to aminoglycosides ( 40 , 41 ). We therefore applied the same approach described for mexZ to fusA1.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally occurring mutations in the fusA1 gene have been linked to enhanced resistance to aminoglycosides ( 40 , 41 ). We therefore applied the same approach described for mexZ to fusA1.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that no statistically significant differences were observed in mexY expression between strains fully susceptible or resistant to one, two or three antibiotic classes, could indicate that other factors influence the expression of antibiotic resistance and/or of MexXY-OprM. Actually, it has recently been demonstrated that mutations in genes other than mexZ (fusA1 and amgRS) have a higher impact on reducing aminoglycoside susceptibility and that combination of mutations in the three genes have a stronger effect 23 . For three patients the type of mexZ mutation correlated with the resistance profile, although the association was inverse to what was expected: strains harbouring wild type mexZ were resistant to 2 classes (not including aminoglycosides) or multiresistant (including aminoglycosides) while double mutants were fully susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was already made twenty years ago but in that case no mutations in mexZ regulator were found 26 , although the authors conclude that MexXY overexpression in aminoglycoside resistant strains occurs via mutation in one or more genes that were not identified at the time of the study. We now know that mutations in fusA1 and amgRS have a greater impact than mexZ in reducing aminoglycoside susceptibility 23 . Few studies have so far analysed gene expression of P. aeruginosa in vivo in patients with CF, either by measuring gene expression directly into clinical samples [42][43][44] or under laboratory conditions mimicking human conditions or animal models 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations